Kekerasan Dalam Rumah Tangga Terhadap Pelaku Judi Online Dalam Perspektif Hukum Positif Dan Fiqih Siyasah - Alexander, Ongky; Setiawan, Alpat Reza; Sasana, Elsa Ilka; Sakina, Rapika; Ngimadudin, Ngimadudin (STAI Bumi Silampari, 2025)
The phenomenon of domestic violence (DV) against online gambling perpetrators is increasingly becoming a concern in the social dynamics of modern society. Online gambling not only has an impact on the personalals involved, but also has serious implications for family stability, including increasing the potential for conflict and domestic violence. This study aims to analyze this phenomenon through the perspective of fiqh siyasah law in order to understand how Islam views and responds to this problem in the context of Islamic politics and government. The research method used is a qualitative approach with library research, where data is obtained from classical and contemporary literature in the fields of fiqh, siyasah syar'iyyah, and laws and regulations related to domestic violence and gambling. The results of the study show that fiqh siyasah has legal instruments and policies that can be used to overcome the negative impacts of online gambling on personalals and families. From an Islamic perspective, gambling is prohibited because it damages the social, economic, and moral order of society. Therefore, the state has a strategic role in protecting families from the impacts of online gambling by implementing preventive and repressive policies in accordance with the principles of siyasah syar'iyyah. The conclusion of this study confirms that domestic violence due to online gambling is a social problem that needs serious attention from the aspect of Islamic law. Fiqh siyasah can be the basis for formulating policies that not only aim to prosecute gambling perpetrators, but also provide protection to families and build a legal system that is more responsive to this problem.